Keselamatan Makanan: Dimensi Zaman, Keperluan dan Kekangan Semasa: Food Safety: Dimensions of Time, Needs and Current Constraints - Md. Ariffin, Mohd Farhan (Online Journal of Research in Islamic Studies, 2020)
Global security and prosperity are closely linked to food safety policies. It was not born in the blink of an eye, in fact it is a systematic idea that looks at the aspects of the well-being of mankind since time immemorial. However, there are still many in the community who fail to understand the importance of food safety knowledge. Accordingly, this study aims to examine the significant side of current food safety studies. To achieve the following objectives, the study analyzes the data inductively and deductively to understand its historical aspects and relevancancy. The results of the study found that food safety has a long history of development and is increasingly complex in line with current advances in food technology.